Pengembangan Sistem Penjualan dan Pembudidayaan Ikan Hias Berbasis Web : Inovasi Teknologi untuk Keberlanjutan Bisnis - Berry Anugrah; Efmi Maiyana (Journal of Information System and Education Development, 2024)
The development of a web-based ornamental fish sales and breeding system is an innovative step to improve operational efficiency and achieve business sustainability. In the context of the ornamental fish business, a web-based platform provides significant advantages, allowing business owners to reach global markets more effectively. The integration of information technology in the sales system not only improves product affordability, but also simplifies transactions and inventory monitoring. In addition, this article discusses the application of monitoring technology for ornamental fish farming, using sensors and automated measurement systems to monitor water quality, temperature, and other environmental parameters. With the development of an integrated web-based system, this article aims to contribute to the development of a sustainable ornamental fish business that is responsive to modern market demands.